Simultaneous optimization of treatment efficiency and operating cost in leachate concentrate degradation by thermal-activated persulfate catalysed with Ag (I): comparison of microwave and conventional heating. Issue 3 (3rd July 2019) - Genç, Nevim; Durna, Elif
Abstract: The present study investigates the treatment of membrane concentrate leachate by thermal-activated persulfate catalysed with Ag(I). Activation of persulfate was done by microwave/conventional heating. The persulfate activation with microwave (MW) and conventional heating (CH) processes was compared with Taguchi multi-response optimization as robust design approach. Parameters affecting the leachate concentrate treatment were determined as required energy for persulfate activation, the oxidation time and concentrations of persulfate anion and Ag(I). With multi-response optimization, maximum chemical oxygen demand (COD) removal, maximum colour removal and minimum operating costs are determined simultaneously. The optimal combination levels for multi-response characteristics were determined as power at 700 W, oxidation time at 4 min, persulfate anion concentration at 187.5 g/L and Ag(I) ion concentration at 0.5 g/l for MW and 80°C, oxidation time at 30 min, 112.5 g/L persulfate anion concentration and Ag(I) ion concentration at 0.25 g/L for CH processes. The optimum combinations were confirmed with confirmation experiments for both processes. In the MW process, COD removal of 53.3%, colour removal of 99.9% and operating cost of 25 €/L wastewater were observed, while in the CH process COD removal of 20%, colour removal of 65.4% and operating cost of 16.5 €/L wastewater were observed.